Strategic trading and trade reporting by corporate insiders - André Betzer; Jasmin Gider; Daniel Metzger; Erik Theissen (University of Cologne, Centre for Financial Research (CFR), 2010)
Regulations in the pre-Sarbanes-Oxley era allowed corporate insiders considerable flexibility in strategically timing their trades and SEC filings, for example, by executing several trades and reporting them jointly after the last trade. We document that even these lax reporting requirements were frequently violated and that the strategic timing of trades and reports was common. Event study abnormal returns are larger after reports of strategic insider trades than after reports of otherwise similar nonstrategic trades. Our results also imply that delayed reporting is detrimental to market efficiency and lend strong support to the more stringent trade reporting requirements established by the Sarbanes-Oxley Act.
Keywords: G14; G30; G32; 330; insider trading; directors' dealings; corporate governance; market efficiency